The Effect of Variations of Shooting Training on Shooting Ability in Players Aged 14-17 Years Victory Dairi Football Club - Candra Fernando Telaumbanua; Ibrahim Ibrahim (Journal of Indonesian Active in Sports, 2024)
The purpose of the study was to determine the effect of various shooting exercises on shooting ability in players aged 14-17 years Victory Dairi football club in 2022. The research method was conducted through an experimental approach with a one-group pre and post-test design. The research instrument used was a shooting test developed by Ardi Nusri through a distance of 11 metres between the position of the ball and the wall as a target. The boxes on the wall that will be targeted are five boxes that have different widths and the same height. Then, what needs to be recorded during the test is the score obtained based on the target box hit by the ball and the time recorded. Scores and time records will be converted into values, accumulated, and categorised. The sample in this study is 12 people who were selected through purposive sampling technique. Data were analysed using normality test and paired t-test at 5% significance level. The results of hypothesis testing through paired t-test obtained the t-count of 12.89. Furthermore, the value was compared with the t-table value with degree of freedom of 11 at the Î± 0.05 significance level which is 2.201. Thus, the t-count is greater than the t- table (12.89> 2.201). These results concluded that there is a significant effect of shooting training variations on the results of football shooting ability in players aged 14-17 years Victory Dairi football club in 2022. For future research, it would be beneficial to consider a larger sample size and include a control group in order to further validate the effectiveness of shooting training variations on shooting ability.